PERENCANAAN MODA TRANSPORTASI UMUM DI KECAMATAN MIJEN KOTA SEMARANG - Sukmana, Khomang; Putro, Saptono (Geo-Image, 2017)
Transportation is an important aspect in society mobility to do their daily activities. This study wants to find out what the trips number (trip generation), where the distribution of trip (trip distribution) and how to plan public transportation in Mijen. Based on the result is the data shows that the number of trips in Mijen is 44,388 trips / day. The distributions of the trips in Mijen are 20,275 trips / day, Mijen to Candi industrial areas are 15,282 trips / day, Mijen to Tambakaji industrial estate are 5581 trips / day, Mijen to the industry in Tugu are 2979 trips / day, Mijen to Pemuda Street are 259 trips / day, Mijen to Johar market are 8 trips/day, Mijen to Simpang Lima are 5 trips / day. And, the users of public transportation in Mijen are 36%. Meanwhile, there are some criteria in selecting public transportation. The data shows that the first priority is salvation, the second is fare, and the third is comfort. The following priorities are security, travel time, frequency of the vehicle, reliability, waiting time and carrying capacity. First alternative of public transportation modes are medium bus. The second is the bus. The following alternatives are small bus and taxi.